Didáctica de la interpretación de textos producidos con códigos no verbales - Sevilla Muñoz, Manuel (Didáctica. Lengua y Literatura, 2003)
In this article the non-verbal codes used in certain sciences, such as Chemistry, Mathematics and Physics, are defined and analysed. The didactics of these codes is stated with an explanation of the steps that should be followed to enunciate the pedagogical objectives, select the didactic material and design the corresponding tasks. A collaboration between the teachers of language and those of different scientific subjects is also proposed in the didactics of the non-verbal codes.